The influence of table tennis training on the physical condition of schoolchildren aged 13-14 years - Baidiuk, Mykola; Koshura, Andrey; Курнишев, Юрій; Vaskan, Ivan; Chubatenko, Sevil; Gorodynskyi, Sergii; Ярмак, Олена (Editura Universitatea din Pitesti, 2019)
The article presents the results of the pedagogical experiment, in which 37 schoolchildren aged 13-14 years took part. The aim of the study was to determine the influence of recreational activity with table tennis means on the physical condition of schoolchildren. For the realization of the goal and the solution of the tasks we used general scientific methods (analysis, synthesis, generalization, comparison), anthropometric methods, physiological methods, psychophysiological methods, methods of mathematical statistics. The proposed recreational program with table tennis means was designed for the period of 10 months, and contained theoretical and practical sections. During the pedagogical experiment, the dynamics of changes in the morphofunctional state and psychophysiological state of schoolchildren aged 13-14 years were observed. During the classes, the anthropometric characteristics of boys and girls changed according to the natural biological processes. Statistical changes (p <0.05) occurred only in the boys in the body mass index, this value increased by 5.6%. Significant changes (p <0.05; p <0.01) in boys and girls are observed in terms of the cardiovascular and respiratory systems. In the boys, at the end of the pedagogical experiment, the average result of the heart rate at rest decreased by 5.5 beats min-1, that equals 6.5 % (p <0.05); in the girls it decreased by 4.5 beats min-1 that equals 5.2 % (p <0.05). A significant increase is observed in the average result of vital lung capacity; in the boys it increased by 0.4 l that equals 17.4 % (p <0.01); in the girls - by 0.3 l, that equals 15.0 % (p <0.01). The latent time of simple reaction for visual and auditory stimuli in boys and girls decreased significantly (p <0.01). The mean group indicator of the complex choice reaction, the short-term memory capacity, the volume of the processed information, and of the sharpened Romberg test, both in boys and girls, has improved significantly (p <0.01).
Вплив занять настільним тенісом на фізичний стан школярів 13-14 років
Keywords: table tennis; physical condition; schoolchildren; настільний теніс; фізичний стан; школярі